Depth Psychology in Short Story „Skoczek” [„Knight”] from the Collection „Gra na wielu bębenkach” [„Playing on Many Drums”] by O. Tokarczuk - Walczak, Marta (Free your mind: Reflections on language, literature and culture, 2022)
The paper is an interpretation of the short story "Skoczek" ["Knight"] from the collection ["Playing on Many Drums"] by Olga Tokarczuk. As the author admits that she reaches for psychological knowledge to understand reality ("The Tender Narrator"), the interpretation includes concepts taken from depth psychology, in particular Carl G. Jung's analytical psychology. The story presents a relationship of aging man and woman who once had deeper feelings for each other, now, however, they stay connected only by recollecting memories of their common past. Tokarczuk shows mutual anger, sorrow and unspeakable resentment between these two people. None of them is able to free themselves from Jung's shadow and end their miserable relationship. While staying at the seaside, a bizarre occurence happens – a chess knight is caught from the sea. This is interpreted by the concept of Jung’s synchronicity, which may be understood as an attempt to force the characters to change their life situation.